PENGARUH BIOMASSA AZOLLA TERHADAP STATUS LOGAM BERAT TIMBAL (Pb) PADA TANAH - Muhammad Abror; Teuku Sabrina; Benny Hidayat (Universitas Sumatera Utara, 2013)
Research on title the effect of Pb-Polluted azolla biomass on polluted on lead heavy metal status at polluted and unpolluted soil with Pb aimed to evaluate the potency of Pb-polluted azolla biomass on the availability of Pb in soil. The experiment design was factorial randomized block design with 2 factors and 3 replications. First factor was Pb-polluted azolla biomass with 3 treatments 0 g/kg, 15 g/kg and 30g/kg, second factor was Pb application with 3 treatments 0 ppm/kg, 150 ppm/kg, and 300 ppm/kg. The parameters was soil pH, organic matter. Pb total and available Pb from 1 week and 2 weeks after applying Pb-polluted azolla. The result showed that application of Pb-polluted azolla biomass increased 20% and 30% the availability of Pb after 1 week compare to control for Pb-polluted azolla treatment 15 g/kg and 30 g/kg respectively. Application of Pb-polluted azolla biomass did not significantly affected the soil pH and increasing soil organic matter. Meanwhile application of Pb polluted azolla biomass on unpolluted soil increased Pb-available about 60% and 85% compare to control for azolla biomass applying 15 g/kg and 30 g/kg, and also increasing soil organic matter content. In the second week, Pb-polluted azolla biomass increased Pb availability in unpolluted soil around 75% and 82% for azolla treatment 15 g/kg and 30 g/kg respectively. Meanwhile in the treatment applying 300 ppm Pb, application of Pb-polluted azolla decreased 8% Pb of available. In general, the effect of application Pb-polluted of azolla biomass increased the amount of Pb available and soil organic matter in the soil and pH decreased with time.